Formation of heterokaryons by fusion of isolated hyphal tips on solid medium in petri plates - A. M. Srb; A. M. Infanger (Fungal Genetics Reports, 1964)
Formation of heterokaryons by fusion of isolated hyphal tips on solid medium in petri plates